Religious Marriage and Its Impact on Family Economic Rights in Islamic Law and Positive Law in Indonesia - Arhaj, Muhammad Fiqhri; Nasibah, Asri Aryanti; Aisyah, Siti Nur; Ajijah Nugraha, Nabila Zahran; Putri, Melva Adinda; Supriyadi, Tedi (Pusat Riset dan Inovasi Nasional, 2025)
This study examines interfaith marriage and its impact on family economic rights from the perspectives of Islamic law and positive law in Indonesia, with a case focus on Sumedang Regency. Employing a qualitative phenomenological approach, the research involved semi-structured interviews with both traditional and modern Islamic scholars, along with an analysis of religious texts and statutory regulations. The findings reveal that the majority of scholars reject interfaith marriage based on Sharia principles and Article 2(1) of Law No. 1 of 1974 on Marriage. Nevertheless, some couples pursue such unions through administrative religious conversion or overseas ceremonies to obtain legal recognition. These practices often result in legal ambiguity regarding economic rights within the family—such as inheritance, joint property, and financial support—and may lead to familial disputes. Additional social consequences include identity confusion among children, community stigma, and potential conflicts within extended families. The study underscores the strategic role of institutions like Islamic boarding schools (pesantren) and the Office of Religious Affairs (KUA) in providing legal education and advocates the need for a responsive civil registration mechanism that acknowledges interfaith marriages while respecting Islamic legal principles. A contextual approach is proposed to bridge the tension between religious norms, legal certainty, and the protection of family economic rights.